The business of fancydancing : stories and poems - Alexie, Sherman, 1966- (Hanging Loose Press, 1992)
A collection of 5 short stories and 40 poems focusing on life on a Native American reservation in eastern Washington state, "that deals comically and poignantly with basketball, convenience stores, cars and other artifacts of everyday life"--New York Times, Notable Books of the Year 1992, December 6, 1992.